INTEGRATION OF THE VALUES OF TAWHID, AMANAH, AND IHSAN IN THE THEORY OF ISLAMIC EDUCATIONAL ORGANIZATION: AN ETHICAL THEOLOGICAL APPROACH - Fil Isnaeni (FAJAR Jurnal Pendidikan Islam, 2026)
This article aims to conceptually analyze organizational theory from the perspective of Islamic values and ethics through the integration of three main principles, namely monotheism, amanah, and ihsan. This study uses a qualitative approach with the library research method. The results of the study show that monotheism functions as an ontological foundation that affirms that the existence of the organization is rooted in divine consciousness and oriented towards falah (success in the world-hereafter). Amanah plays a role as an epistemological principle that guides organizational governance based on justice, honesty, and moral responsibility. Meanwhile, ihsan is an axiological dimension that shapes the performance ethics and culture of professional organizations based on sincerity and spiritual awareness. The integration of these three values resulted in a holistic and equitable model of Islamic organizational theory, combining the rationality of modern management with Islamic spirituality. Implicitly, this theory not only enriches the academic discourse of Islamic management, but also offers a practical paradigm in building an organization that is efficient, moral, and oriented towards the benefit of the ummah (rahmatan lil 'alamin).